Hypotestosteronaemia in the aging male: should we treat it? (Swiss Medical Weekly, 2015)
The term male hypogonadism is defined as the failure to maintain physiological concentrations of testosterone, a physiological quantity of sperm or the combination of both. Aetiologically, androgen deficiency can originate from the testes (primary hypogonadism) or from the hypothalamic-pituitary regulation of the testicular function (secondary hypogonadism). The causes of hypogonadism are very diverse and may be genetically determined (e.g. Klinefelter’s syndrome) or acquired (tumours, infections, haemochromatosis). Classical hypogonadism linked to an underlying disease, such as a pituitary tumour, is a distinct indication for androgen substitution. But how about the aging male? It is known that there is a highly variable age-related decline in testosterone levels; whether this represents a variation of normality or has a true disease value requiring therapy has been disputed over more than a decade. The key questions surrounding this debate concern not only the age-dependent threshold for serum testosterone but, more importantly, the risks and benefits of testosterone replacement therapy in the aging male. We searched the literature for randomised controlled trials of testosterone administration in aging males with a size of at least 100 patients and a follow-up of at least 6 months, and identified eight studies. These studies mostly tried to evaluate the effect of testosterone on bone density, muscle strength and body composition, rather than clinically meaningful endpoints. Moreover, these trials have provided evidence for relevant cardiovascular adverse events in elderly men. This supports the need for further studies to define the treatment threshold for testosterone levels in the aging male, as well as with regard to the long-term risks and relevant benefits of testosterone therapy in this population. Until we have more solid data in aging males, testing for testosterone deficiency and testosterone replacement should remain reserved for patients with predisposing conditions, symptoms and signs of bona fidehypogonadism.